2022
DOI: 10.1007/s11430-021-9936-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron loss of paddy soil in China and its environmental implications

Abstract: Iron (Fe) is an important element for the terrestrial and marine ecosystems through its biogeochemical cycling on the Earth's surface. China has a long rice cultivation history, with extensive rice distribution across many types of paddy soils. Paddy soils are the largest anthropogenic wetlands on earth with critical roles in ecosystem functions. The periodic artificial submergence and drainage during paddy soil evolution result in significant changes in soil moisture regime and redox conditions from the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Soil profile Fe represents a significant reservoir in the global iron cycle; however, estimations of soil profile Fe loss from paddy fields are often overlooked (Chen et al, 2022). In this study, we estimated that the soil profile (0−100 cm) of all woodland converted to paddy fields in the southern subtropical zone of China may experience a loss of 2 872 Tg of Fe t while accumulating 694 Tg of SOC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Soil profile Fe represents a significant reservoir in the global iron cycle; however, estimations of soil profile Fe loss from paddy fields are often overlooked (Chen et al, 2022). In this study, we estimated that the soil profile (0−100 cm) of all woodland converted to paddy fields in the southern subtropical zone of China may experience a loss of 2 872 Tg of Fe t while accumulating 694 Tg of SOC.…”
Section: Discussionmentioning
confidence: 96%
“…Paddy fields are characterized by frequent redox fluctuations, which may drive C cycling and result in the production and transportation of different Fe forms (Li et al, 2019). Further exploration is needed to understand the long-term loss of Fe under rice cultivation at regional scales and the contribution of different forms of Fe (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Paddy soils constitute the largest anthropogenic wetlands worldwide . The redox-alternating conditions during rice planting are the main factors controlling soil Fe loss, which is strongly linked to biogeochemical cycling on the Earth’s surface. The uptake strategies and sources of Fe plaque and soil solutions in paddy rice were identified using Fe isotopes. , Rice undergoes Fe excess and restriction in the soil solution during typical flooding–drainage alternation during rice growth; however, the uptake mechanisms underlying the redox-alternating conditions remain largely unknown. This study indicated that Fe­(III) uptake from Fe plaques predominantly occurs via strategy II during the flooding periods, and its contribution generally increases during the vegetative stages.…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, the main subject of studies on cyberbullying and social media use is focused on teenagers and children, putting more emphasis on school education and parental influence as approaches to civilizing cyberspace (Palfrey, 2010). In addition, taking Germany as a case in point, netizens' mental and physical health is also taken care of as a result of governmental efforts (Chen & Song, 2022). In another study, social well-being regarding universal access is brought to attention (Berg, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, there are discussions over the influence of public opinion. Studies on regulating public opinions have been regarded as essential and forceful regulations on public opinions have proven effective (Chen & Song, 2022). In China, studies on public policy at a macro level can be separated into domains including the government, legislation, platforms, and society.…”
Section: Literature Reviewmentioning
confidence: 99%